2013
DOI: 10.1186/1471-2199-14-15
|View full text |Cite
|
Sign up to set email alerts
|

Loss of CARM1 is linked to reduced HuR function in replicative senescence

Abstract: BackgroundThe co-activator-associated arginine methyltransferase 1 (CARM1) catalyzes the methylation of HuR. However, the functional impact of this modification is not fully understood. Here, we investigated the influence of HuR methylation by CARM1 upon the turnover of HuR target mRNAs encoding senescence-regulatory proteins.ResultsChanging the methylation status of HuR in HeLa cells by either silencing CARM1 or mutating the major methylation site (R217K) greatly diminished the effect of HuR in regulating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 31 publications
0
45
0
Order By: Relevance
“…These are two of the widely used senescence markers known to increase with aging in several rodent and human tissues and most importantly in alveolar epithelial cells of COPD patients (41,47,48). Moreover, previous studies showed CARM1-dependent posttranslational methylation of HuR enhancing its association with p16 or p21 mRNA and leading to transcript degradation, whereas absence of CARM1 led to transcript stabilization (22,24,49). The impact of CARM1-mediated regulation on senescence was confirmed by increased numbers of β-galactosidase positive alveolar epithelial cells, which was augmented after CSE stimulation demonstrating that CARM1 deficiency could further enhance the senescence induction following injury stimulus in ATII cells.…”
Section: Interestingly Carm1 Was Downregulated In Atii Cells Of Emphmentioning
confidence: 95%
See 3 more Smart Citations
“…These are two of the widely used senescence markers known to increase with aging in several rodent and human tissues and most importantly in alveolar epithelial cells of COPD patients (41,47,48). Moreover, previous studies showed CARM1-dependent posttranslational methylation of HuR enhancing its association with p16 or p21 mRNA and leading to transcript degradation, whereas absence of CARM1 led to transcript stabilization (22,24,49). The impact of CARM1-mediated regulation on senescence was confirmed by increased numbers of β-galactosidase positive alveolar epithelial cells, which was augmented after CSE stimulation demonstrating that CARM1 deficiency could further enhance the senescence induction following injury stimulus in ATII cells.…”
Section: Interestingly Carm1 Was Downregulated In Atii Cells Of Emphmentioning
confidence: 95%
“…Interestingly, CARM1-dependent methylated HuR is reported to stabilize SIRT1 transcript (22,23). Therefore, we investigated whether reduced CARM1 could regulate alveolar epithelial cell senescence in emphysematous lungs by modulating SIRT1.…”
Section: Reduced Carm1 Contributed To Senescence Of Lung Alveolar Epimentioning
confidence: 99%
See 2 more Smart Citations
“…However, its role in RNA-binding appears complex as methylated ELAVL1 is proposed to concomitantly increase and decrease the stability of some mRNAs (e.g. cyclin A and cyclindependent kinase inhibitor 2A (CDKN2A) respectively) to inhibit replicative senescence [29]. Surprisingly, a role for arginine methylation in the best studied function of ELAVL1 in promoting mRNA translation and stability (i.e.…”
Section: Elavl1/hu-antigen Rmentioning
confidence: 99%